Jesus The Teacher - Sigiro, Adi Suhenra (Sekolah Tinggi Teologi Hagiasmos Mission, 2023)
After reading the book, the writer found that Jesus knew His identity as Teacher and God. Therefore, the purpose of His coming into this world is to teach the truth to humans both through what is delivered and the example of His life. Therefore, a teacher must really realize, accept and be proud of his duties as a teacher so that he can carry out his duties to the fullest and be able to be an example for other students and society. Through reading this book, by learning from the Lord Jesus, there are many principles that a teacher must have and work on in teaching, namely knowing his students correctly with all the developments and struggles they face. In addition, a teacher must have clear goals, so that the learning process does not take place and act just like that without producing anything in students. In teaching a teacher, one must use the Bible as the main source in teaching even though one must be open to other knowledge to add insight to the teacher and students. A teacher must improve the quality of himself in teaching, by preparing both materially and choosing the right methods and strategies to use that are in accordance with the ability of students to accept them. In teaching a teacher must have a long-term vision in students. So that this helps the teacher to be patient and continue to give the best even though the students still have various weaknesses and deficiencies in themselves. Teachers must be able to see the positive side in students and develop it so that it becomes an impactful ability for the students themselves and the wider community in the future. Through reading this book, a teacher is required to learn from the person of the Lord Jesus and have a good personal relationship so that the wisdom and anointing from the Lord Jesus equips the teacher in carrying out his duties.